Study of ground water quality in tap and hand pump water of Tonk city, Rajasthan, India - Soni, Shyam; Singh, R.K. (International Journal of Scientific Research and Management (IJSRM), 2018)
Water is basic need of life for all living organism at the earth. To study the drinking water pollution in Tonk city of Rajasthan (India), a total of five water samples were collected from tap and hand pump of various area of tonk city. The various physical chemical parameters such as pH, chloride, total alkalinity, total dissolved solid and total hardness were analyzed in the water samples to characterize the ground water quality and suitability for drinking purpose. All the water samples were compared with Indian standard of drinking water prescribed by bureau of Indian standard BIS 10500:2012. The physical chemical analysis of water samples of Tonk city showed that pH value ranged from 7.00 to 7.60 and chloride ranged from 2750.24 to 595.96 mg/l. The total alkalinity varied from 185.90 to 452.25 mg/l. The total dissolved solid ranged from 270 to 2550 mg/l and total hardness from 146 to 162 .14 mg/l. mg/l. The result of physical chemical analysis of water samples of Tonk city indicated that tap water of Jawahar Bazaar Tonk (S1) and Taj colony Tonk (S2) were suitable for drinking purpose and hand pump water of Takhata (S3), Mehandi bagh (S4), Civil line Tonk (S5) were unsuitable for drinking purpose. This study thus concludes that hand pump water in study area is chemically unsuitable for drinking. It is recommended to carry out a proper and continuous water quality program and development of effective management practices for utilization of water resources.